2005
DOI: 10.3354/meps304201
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Sr/Ca ratios in the otoliths of two marine eels, Gymnothorax reticularis and Muraenesox cinereus, during metamorphosis

Abstract: Sr/Ca ratios in the otoliths of 2 marine eels, the moray eel Gymnothorax reticularis and the pike eel Muraenesox cinereus, decreased greatly when the crystal structure of otolith daily growth increments changed from concentric to radiate form. This decrease is proposed to correspond to the timing of metamorphosis from the leptocephalus to glass eel stage, similar to freshwater eels (Anguilla spp.). In freshwater eels, ontogenetic and habitat shifts might influence the decrease. However, marine eels do not migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 24 publications
2
11
0
Order By: Relevance
“…The other tropical and temperate species of glass eels that have been examined generally have larval durations within this range (see Aoyama 2009 for a recent review), but the European eel may have a longer larval duration than any other species (see Kuroki et al 2008b). The same pattern of increment widths during metamorphosis has been observed in the Atlantic species of Conger, whose ages at metamorphosis have been estimated using this method (Correia et al 2003(Correia et al , 2004 and in a species of muraenid (Ling et al 2005).…”
Section: Aqua-bioscience Monographs Vol 2 No 4 2009mentioning
confidence: 87%
“…The other tropical and temperate species of glass eels that have been examined generally have larval durations within this range (see Aoyama 2009 for a recent review), but the European eel may have a longer larval duration than any other species (see Kuroki et al 2008b). The same pattern of increment widths during metamorphosis has been observed in the Atlantic species of Conger, whose ages at metamorphosis have been estimated using this method (Correia et al 2003(Correia et al , 2004 and in a species of muraenid (Ling et al 2005).…”
Section: Aqua-bioscience Monographs Vol 2 No 4 2009mentioning
confidence: 87%
“…Indeed, for the flatfish Solea solea (L. 1758), specimens shift to a benthic life after metamorphosis and the drop in Sr:Ca that was observed during this change was attributed to a high metabolic rate rather than a shift from a marine to an estuarine location (De Pontual et al , 2003). For two marine eels [ Gymnothorax reticularis Bloch 1795 and Muraenesox cinereus (Forsskål 1775)], the Sr:Ca ratio decreases during metamorphosis although they are strictly marine species (Ling et al , 2005). In this study, however, the low Sr:Ca values observed from the metamorphosis check mark to the edge of the otolith were consistent with those attributed to a freshwater habitat occupation in Anguillidae (Tabouret et al , 2010), Rhinogobius (Tsunagawa & Arai, 2008) and Sicydiinae species (Radtke & Kinzie, 1996; Shen & Tzeng, 2002; Chang et al , 2006).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Gilbert et al (2005) estimated the density and biomass of moray eels (Muraenidae). In another study, Ling reported a decrease in the Sr/Ca ratios in the otoliths of Gymnothorax reticularis during metamorphosis (Ling et al, 2005). In addition, Tamburrini et al (2001) studied the structure/function relationships of the brown moray (Gymnothorax unicolor) hemoglobin system.…”
Section: Introductionmentioning
confidence: 99%